Multiple sclerosis risk perception and acceptance for Brazilian patients - Denis Bernardi Bichuetti; Carolina Azze Franco; Isaac Elias; Andreia C. R. Mendonça; Lorraine Fiama Diniz Carvalho; Denise Sisterolli Diniz; Carmen Tur; Mar Tintoré; Enedina Maria Lobato de Oliveira (Arquivos de Neuro-Psiquiatria)
ABSTRACT The perception of multiple sclerosis (MS) severity and risk associated with therapies might influence shared decision making in different countries. We investigated the perception of MS severity and factors associated with risk acceptance in Brazil in 96 patients with relapsing-remitting MS using a standardized questionnaire and compared this with two European cohorts. Multiple sclerosis was perceived as a very severe disease and the risk of developing progressive multifocal leukoencephalopathy due to natalizumab was seen as moderate to high. Seventy-six percent considered a risk of 1:1,000, or higher, an impediment for natalizumab use. Older age was the only variable associated with higher risk acceptance and our patients showed a more conservative profile than German and Spanish patients. Our patients perceived MS severity and progressive multifocal leukoencephalopathy risk similarly to elsewhere, but their willingness to take risks was more conservative. This should be considered when discussing therapeutic options and it might have an impact on guideline adaptations.